Ανακύκλωση και χρήση βιομηχανικών αποβλήτων και περισσευμάτων στη Κυπριακή βιομηχανία τροφίμων και ποτών για παράγωγη βιοκαυσίμων - Καραολής, Κωνσταντίνος (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
This dissertation is examining the recycling and the use of industrial waste and leftovers in Cyprus food and beverage industry for the production of biofuels. The purpose of the following work is an extensive research in various industrial units of food and beverages in Cyprus, even in restaurants or farms, whether the industrial waste or leftovers are reused or recycled. A brief introduction to the global energy crisis and the need to find new sources of energy other than oil was first examined. A further examination of the production of biofuels was then followed. In Chapter 2 there is a reference to the types of waste in Cyprus and waste management. In Chapter 4 a research is being made with the form of a questionnaire for the industrial waste in Cyprus. The aim of this study was to see whether our industries are informed about the various Renewable Energy Sources (RES), if they use any of them and if not whether they are interested to use them, as well as the type and the quantity of their waste. Chapter 5 is a brief reference to livestock and livestock management system both in Cyprus and abroad, followed by present various statistical surveys in relation to the total number of biodegradable waste in the European Union and the overall consumption of electricity from renewable energy and bioelectricity in the EU Chapter 6 contains a brief reference to the regulation and continues (Chapter 7), with the methods of treatment and use of treated waste. Chapter 8 describes the visit to a Plant in Cyprus where electricity from animal waste is produced. The work continues (Chapter 9), with an economic evaluation and various suggestions that could be implemented. Subsequently, Chapter 10 reports new / ideas and methods that could be applied in Cyprus both in the field of biofuels and renewable energy in general. Finally, the paper ends with conclusions reached through this research and discusses why the state should promote the use of animal waste and the use of biofuels in general.
Keywords: Βιοκαύσιμα; Βιομηχανικά Απόβλητα; Ζωικά Απόβλητα; Ανακύκλωση; Biofuels; Industrial Waste; Animal Waste; Recycling